Training characteristics and performance of two male elite short-distance triathletes: From junior to "world-class" - Cejuela, R.; Selles-Perez, S. (Scandinavian Journal of Medicine & Science in Sports, 2023)
Objective The sports-science literature lacks data on training and performance characteristics of international elite athletes over multiple seasons. The present case study provided general training characteristics and performance data of two male short-distance triathletes in the Junior, U23, and international Elite categories.